2018
DOI: 10.3329/dmcj.v6i2.38218
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress among Nurses in a Public Medical College Hospital

Abstract: Background: Now a days, there is increased demand and progress in the nursing profession. Along with these stress among the nurses has also increased.Objective: Purpose of the study was to assess the extent of perceived occupational stress and its association with work-related and non-work related causes among nurses.Materials and method: This Cross-sectional study was carried out among 197 nurses of Shaheed Suhrawardy Medical College hospital (ShSMCH), Dhaka, Bangladesh, from the period of 1st July 2015 to 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…The odds of having a higher level of work ability among BSC nurses decreased by 79% compared to those nurses of MSC holders. This finding was supported by a study conducted in Poland, Croatia and Bangladesh [ 37 , 43 , 44 ]. The possible justification might be that people with lower levels of educational status commonly take on work involving more physical labor than those with higher education, which might contribute to unhealthy work practices in employees [ 45 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The odds of having a higher level of work ability among BSC nurses decreased by 79% compared to those nurses of MSC holders. This finding was supported by a study conducted in Poland, Croatia and Bangladesh [ 37 , 43 , 44 ]. The possible justification might be that people with lower levels of educational status commonly take on work involving more physical labor than those with higher education, which might contribute to unhealthy work practices in employees [ 45 ].…”
Section: Discussionsupporting
confidence: 65%
“…The finding of this study revealed that the prevalence of poor level of work ability was higher than the study done in Bangladesh (7.1%) [ 37 ]. The possible explanations for these discrepancies could be methodological differences, like sample size and study area.…”
Section: Discussionmentioning
confidence: 59%
“…Pada pertengahan tahun 1950, stress dianggap sebagai salah satu bahaya dalam pekerjaan. Dalam hal ini, stress kerja perawat akan berkontribusi dalam masalah kehadiran kerja dari perawat serta angka turn over yang pada akhirnya stress kerja ini akan mempengaruhi tingkat kepuasan kerja perawat dan kualitas pelayanan keperawatan yang dilakukan oleh perawat kepada pasien (Das, Biswas, & Afrin, 2018). Pada tahun 1996 World Health Organization (WHO) menyatakan bahwa stress sebagai epidemi dunia di abad 21 (Herqutanto, Harsono, Damayanti, & Setiawati, 2017).…”
Section: Pendahuluanunclassified